Occupational Diesel Exposure and Brain Tumors: A Systematic Review and Meta-Analysis - Sassano, Michele; Collatuzzo, Giulia; Teglia, Federica; Boffetta, Paolo (La Medicina del Lavoro, 2025)
Diesel exhaust (DE) is recognized as a carcinogen for the lungs, although evidence linking it to adult brain tumors is limited. We aimed to systematically review the evidence regarding the association between occupational DE exposure and adult brain and other central nervous system (CNS) tumors. A systematic literature review was conducted to identify cohort studies on occupational DE exposure and the risk of adult cancers other than lung cancer. We meta-analyzed relative risks (RRs) and 95% confidence intervals (CIs) for brain or CNS tumors using the DerSimonian and Laird random-effects model. Fourteen studies were included in the meta-analysis. The results showed no in-creased risk of brain or CNS tumors among workers exposed to DE (RR: 0.99; 95% CI: 0.91, 1.07). Findings were consistent when analyzing studies based on incidence (RR: 0.96; 95% CI: 0.90, 1.03; six studies) and mortality (RR: 1.09; 95% CI: 0.87, 1.37; nine studies) separately, as well as in subgroup analyses based on sex, publication year, geographic region, and study quality score. No evidence of publication bias was found (p=0.244). The findings of our meta-analysis suggest that occupational DE exposure is not associated with adult brain or CNS tumors. Given the limitations of the included studies, these results should be interpreted with caution.